The Impact of Using English Songs Towards the Students’ Vocabulary Mastery at Grade Ten of SMK Negeri 1 Bandar Lampung in Academic Year 2013 - 2014 - Bastian Sugandi (Bandar Lampung University (UBL), 2014)
The objective of this research was to find out the impact of using English songs towards the students’ vocabulary mastery at grade 10 of SMK Negeri 1 Bandarlampung 2013 - 2014.Vocabulary mastery is all the words known and used by a particular person. The use of English songs in the teaching and learning processes is expected to be able to improve the students’ vocabulary mastery.Data analysis was attempted using t-Test for two group design. Results indicated that p-value 1% = 2.65, 5% = 2.00, and t-value = 11,61. It is statistically significant as p-value is smaller than t-value. Therefore, null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. These findings suggest that there is impact of English songs towards the students’ vocabulary mastery at grade ten of SMK Negeri 1 Bandarlampung in academic year 2013 - 2014.